The Effect of Current Ratio and Return on Assets on Stock Returns for Telecommunications Companies Listed on the Indonesian Stock Exchange (IDX) from 2019 To 2024 - Sopi Nuraeni; Dheri Febiyani Lestari (Jurnal Manajemen dan Profesional, 2026)
This study aims to analyze the effect of the Current Ratio (CR) and Return on Assets (ROA) on stock returns in telecommunications sector companies listed on the Indonesia Stock Exchange during the 2019–2024 period. The study uses a quantitative method with secondary data obtained from company financial statements and stock prices. The research sample was determined using purposive sampling techniques and analyzed through multiple linear regression. The results of the study indicate that the Current Ratio has a negative and significant effect on stock returns, while Return on Assets has a positive and significant effect on stock returns. Simultaneously, both variables have a significant effect on stock returns. This study shows that liquidity and profitability are important factors in investor considerations.